Sensitization to emotional chills - Lavrador, L.; Arriaga, P.; Esteves, F. (Second European Society for Cognitive and Affective Neuroscience (ESCAN) Conference, 2014)
The study of chills and goosebumps as emotional reactions is a recent phenomenon. Although different emotions, pleasant and unpleasant, have been associated with the elicitation of chills, most studies consider them as indicators of emotional arousal. In a recent study, Benedek and Kaernbach (2011) observed an increase in the frequency of chills after exposure to emotional relevant stimuli, indicating a sensitization process. The aim of the present study was to test the possibility of increasing the occurrence of this response to highly emotional stimuli through a process of sensitization. Forty-nine participants were randomly distributed by two conditions: a sensitization condition, where they had to report online during five days their chilling experiences and associated contexts, and a control condition, without this sensitization process. After this period, all participants were submitted to the same experimental situation, in which they were exposed to emotional relevant visual and auditory stimulation. Psychophysiological responses (skin conductance level and piloerection) were collected continuously and subjective verbal evaluations were gathered after the exposure. The results showed a general increase of the skin conductance level and piloerection, both to positive and negative stimuli, but no effect of the sensitization manipulation. Regarding the subjective evaluation, there was a clear positive correlation between the reported arousal and the intensity of the chilling experience. It can be concluded that the study of the conditions of elicitation and significance of this emotional reaction deserves further attention.